Relacje aranżera i spółki celowej w transakcjach sekurytyzacji aktywów - poszukiwanie granic firmy - Lizińska, Joanna (Relations between Originator and Special Purpose Vehicle in Securitization Transactions - Searching for Boundaries of the Firm, 2007)
An analysis of relations between originator and special purpose vehicle in asset Securitization should not be focused only on formal contracts established in the structure of transaction. SPV should be a bankruptcy-remote third-party entity. The key element of the independence of the SPY is "true sale" of assets without any recourse. It also means that the sponsor should not provide any recourse. Taking such actions, the sponsor realizes his obligations based upon non-formal contracts and confirms that the risk inherent in the securitized assets was not transferred. Then arises a question about the true independence of the SPY, the question about boundaries of the firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 241-248